Procedure for forming intercultural competence in the general competency structure of training specialist in the sphere of fashion design - Рябчикова, К. М. (Scientific notes of the pedagogical department, 2018)
The main components of competencies for training specialists in the field of fashion design in terms of ensuring the implementation of integral competence are determined. General professional and specially professional competences are allotted. The directions of drawing up structural and logical schemes of preparation for the provision of basic competences are given. The expediency of providing intercultural competence within the structure of professional competencies is proved. If we take for granted the global nature of the processes currently taking place in all areas, the mobility of professionals and students, their desire to find their place in the process of working in different corners of the world, there is a need to form a specific competence associated with the formation of abilities without difficulty to adapt to work in a culture, the other from culture, in which learning took place. This determines the need for the introduction of intercultural competency in the training of specialists. The article substantiates the main general professional and specific professional competencies in the existing plans of training designers of clothing. Structural-logical scheme of formation of necessary competencies was developed, inadequate and unformed communications and blocks were found. The necessity of forming intercultural competency, which ensures the competitiveness of the specialist in the international labor market, is substantiated. Possible formalized approaches to the formation of intercultural competence in the process of training designers of clothing have been developed. The logical schemes for the formation of intercultural competence are singled out: in the form of a parallel structure in which intercultural competence is formed along with other professional competences; consistent, in which intercultural competence is formed as a consequence of basic professional competencies; parallel individual, when intercultural competence is formed within individual professional competencies and combined, combining the basic features of others.